Frequency of safety signals from scientific reports, manufactures, registers, and other sources for a random selection of hip and knee prostheses - Yijun Ren; Lotje A Hoogervorst; Enrico G Caiani; Perla J Marang-van de Mheen; James A Smith; Alan G Fraser; Rob G H H Nelissen; Anne Lübbeke (Acta Orthopaedica)
Background and purpose: The safety and performance of hip and knee prostheses can be assessed by analyzing peer-reviewed literature, registry reports, and safety notices published by national competent authorities/regulatory agencies, or manufacturers. The percentage of hip and knee prostheses with a safety signal published through any of these data sources is unknown. We aimed to assess the frequency of signals identified for a random sample of 10 hip stems, 10 hip cups, and 10 knee implants. Methods: 3 literature libraries were searched to find safety signals defined as information on patterns/occurrences that may alter the device’s benefit–risk profile, reported in peer-reviewed publications for the randomly selected implants. Annual registry reports from 5 national registries were examined to check whether any of the selected implants had outlier performance. The CORE-MD post-market surveillance (PMS) tool was used to collect all related safety notices from 13 competent authority/regulatory agency websites. Manufacturers’ websites were screened for any reported safety information. Results: Safety signals were identified for 21 of the 30 randomly selected implants: 18 identified by registries, 7 by the CORE-MD PMS tool, and 8 based on literature, with 10 implants identified by multiple sources. There was no systematic pattern in timing of publication with a particular source publishing safety signals earlier than other sources. Conclusion: 70% of the randomly selected hip and knee prostheses had ≥ 1 safety signals published, with registries as the source for the majority. No single source identified all 21 implants with signals, which highlights the need for a comprehensive surveillance strategy to aggregate safety signals from multiple sources.